Revisiting “Speak White”: A lieu de mémoire Lost and Found in Translation - Ruschiensky, Carmen (TTR, 2018)
This article traces the afterlives of Michèle Lalonde’s 1968 poem “Speak White” to explore how translation contributes to constructing, renewing and transforming it as a lieu de mémoire through various transformative processes. The term “translation” here designates a phenomenon that includes but extends beyond the concept of translation as linguistic transfer to encompass different forms of rewriting, adaptation and remediation, foregrounding the generative aspect of the memory site as well as the tension between past and present, between a lieu de départ and its reinscription in a new context. Specifically, it focuses on two English translations of “Speak White” that attempt to reconstruct the poem’s subversive diglossia; Marco Micone’s 1989 poem “Speak What,” as a rewriting that takes the form of serious parody; two adaptations produced during the 2012 Quebec Student Strike, “Speak Red” and “Speak rich en tabarnaque”; and the latest incarnation of “Speak White” in Robert Lepage’s 887, a theatrical production that introduces its own layers of intertemporal, intermedial and interlingual complexity. These recreations of “Speak White” reveal how a lieu de mémoire can be simultaneously anchored or re-anchored in the past while also being renewed or rerouted through translation in the present across languages, cultures, media and time.